Helicobacter pylori eradication therapy to prevent gastric cancer: systematic review and meta-analysis. Issue 12 (23rd March 2020) - Ford, Alexander Charles; Yuan, Yuhong; Moayyedi, Paul
Abstract : Objectives: Gastric cancer is strongly associated with Helicobacter pylori ( H. pylori ). We conducted a previous systematic review and meta-analysis that suggested eradication therapy reduced future incidence of gastric cancer, but effect size was uncertain, and there was no reduction in gastric cancer-related mortality. We updated this meta-analysis, as more data has accumulated. We also evaluated impact of eradication therapy on future risk of gastric cancer in patients having endoscopic mucosal resection for gastric neoplasia. Design: We searched the medical literature through February 2020 to identify randomised controlled trials (RCTs) examining effect of eradication therapy on subsequent occurrence of gastric cancer in healthy H. pylori -positive adults, and in H. pylori -positive patients with gastric neoplasia undergoing endoscopic mucosal resection. The control arm received placebo or no treatment. Follow-up was for ≥2 years. We estimated the relative risk (RR) number needed to treat (NNT), and evaluated the disability-adjusted life-years (DALYs) gained from screening from the meta-analysis. Results: We identified 10 RCTs, seven recruited 8323 healthy individuals, and three randomised 1841 patients with gastric neoplasia. In healthy individuals, eradication therapy reduced incidence of gastric cancer (RR=0.54; 95% CI 0.40 to 0.72, NNT=72), and reduced mortality from gastric cancer (RR=0.61; 95% CI 0.40 to 0.92, NNT=135), but did not affect all-cause mortality. These data suggest that 8 743 815 DALYs (95% CI 5 646 173 to 11 847 456) would be gained if population screening and treatment was implemented globally. In patients with gastric neoplasia, eradication therapy also reduced incidence of future gastric cancer (RR=0.49; 95% CI 0.34 to 0.70, NNT=21). Adverse events were incompletely reported. Conclusion: There is moderate evidence to suggest that H. pylori eradication therapy reduces the incidence of gastric cancer in healthy individuals and patients with gastric neoplasia in East Asian countries. There also appears to be a reduction in gastric cancer-related mortality.